The Place of Civilized Words in Arabic School Dictionaries - A Descriptive Reading in the Lexical vocabulary- - Hadj Henni, Mohamed; Rougab, Djamila (LANGUAGE ART, 2025)
The nature of lexical entries varies depending on the nature of the dictionary and the type of target reader, just as general dictionaries include vocabulary that is used by all speakers of the language in various discourses, the Specialized dictionaries include scientific terms used by specialists in various fields of human knowledge, in addition to these two types of entries, we find a third type, which is the Civilized Words that modern dictionaries seek to include in their texts, with the aim of increasing the linguistic stock of speakers, especially students. In this context comes this study, which aims to analyze the texts of school dictionaries, reveal the role of their content in developing the language learner’s language, and highlight its cognitive importance. This is done by determining the extent of Arabic school dictionaries’ familiarity with cultural terms, and recording the extent to which they keep pace with scientific and cultural progress by including these special vocabulary, controlling their meanings, and introducing young people to their meanings, with the aim of reducing the large gap between the language of the home and the street, and what the student receives in school.